Exploring Language Assessment and Testing: Language in Action - Erik Voss (Working Papers in Applied Linguistics and TESOL, 2015)
Many of the current textbooks on language testing in use today take a broad approach covering theory of language ability, test development, and test evaluation, including statistical computations. In his new book, Exploring Language Assessment and Testing, Anthony Green successfully presents an overview of past and current issues in language testing with a focus on classroom-based assessment. With an eye toward promoting assessment literacy, Green has written in a way that is easy to understand as well as intellectually engaging. This book is part of the Introductions to Applied Linguistics series by Routledge, which is intended for graduate students in teacher-education courses. Without a doubt, the novice reader will find the material informative and useful.